Prevalence of palatine torus, mandibular torus and oral exostosis in patients attended at the clinic of the faculty of dentistry of the private university of the east - Lezcano, Liza Graciela Brítez; D'Alessandro, Hada; Paredes, Eliza González; de Olmedo, María Luisa Hermosilla (Seven Editora, 2023)
Background: These excre benign conditions in the oral cavity due to bony growths of the protuberance type known as hyperostosis; they are found mainly at the level of the bony palate and mandibular region. Objective: This study was conducted with the objective of determining the prevalence of palatine torus, mandibular torus and oral exostosis in patients attending the clinic of the Faculty of Dentistry of the Universidad Privada del Este. Materials and methods: A cross-sectional observational study was conducted in the clinic of the Faculty of Dentistry of the Universidad Privada del Este. A sample of 137 patients was selected over a period of 2022 – 2023. Demographic information was collected from patients, such as age and gender. It was evaluated by means of an intraoral and radiographic clinical examination performed by the students. The collected data were statistically analyzed using chi-square tests to determine prevalence. Results: It was obtained from the studied population that 42% (n: 58) of the population has palatine torus (PT), while the Mandibular Torus (TM) of 21% (n: 29), 7 % (n: 10) with Oral Exostosis (EB) and 14% (n: 20) associated PT and TM and EB with some type of T was 4% (n: 5). Discussion: There is a higher prevalence of palatine torus in the female gender 68% (n:38), while the mandibular torus has a higher prevalence in the male gender 59% (n:17). Regarding oral exostosis, a relatively low prevalence was found in the sample studied.DOI:https://doi.org/10.56238/uniknowindevolp-037